(untitled) (Sebha University Conference Proceedings, 2022)
The current research aims to identify the level of commitment to academic and professional integrity among faculty members in the faculties of sebha university. It also aims to reveal the nature of the relationship between academic integrity and professional integrity. The study sample included (75) faculty members who are studying at the undergraduate and postgraduate levels from various faculties of sebha university (arts, science, commerce and political science, nursing, energy and mining), and appropriate statistical methods and means (spss) were used to analyze and process data. The most important of which are: (arithmetic mean - standard deviation - test (t) - pearson’s linear correlation coefficient - spearman’s equation to find the stability coefficient for a test). Also, there are no statistically significant differences in the level of academic and professional integrity of a faculty member in the faculties of sebha university, according to the variables (type - the college - academic qualification - experience) while there are significant differences in the level of academic and professional integrity of faculty members in the faculties of sebha university and in the total score of the questionnaire.